2013
DOI: 10.1038/tp.2013.102
|View full text |Cite
|
Sign up to set email alerts
|

Loss of serum IGF-I input to the brain as an early biomarker of disease onset in Alzheimer mice

Abstract: Circulating insulin-like growth factor I (IGF-I) enters the brain and promotes clearance of amyloid peptides known to accumulate in Alzheimer's disease (AD) brains. Both patients and mouse models of AD show decreased level of circulating IGF-I enter the brain as evidenced by a lower ratio of cerebrospinal fluid/plasma IGF-I. Importantly, in presymptomatic AD mice this reduction is already manifested as a decreased brain input of serum IGF-I in response to environmental enrichment. To explore a potential diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 38 publications
7
55
0
1
Order By: Relevance
“…IGF-1, to our knowledge, has not yet been found effective in enhancing memory in healthy conditions (Stern et al 2014). However, studies in both humans and rodent models reported a rescuing effect of IGF-1, as well as insulin or IGF-2, on cognitive functions in pathological conditions, particularly in cerebrovascular alterations and its role in aging and AD (Liu et al 2001, 2004; Carro et al 2002; Fernandez and Torres-Aleman 2012; Torres-Aleman 2012; Johansson et al 2013; Trueba-Saiz et al 2013), suggesting that IGF-1 and IGF-2 act via distinct mechanisms. Although IGF-1 has been reported to improve memory deficits in aging the data are controversial (for excellent reviews of this subject see Deak and Sonntag 2012 and Sonntag et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1, to our knowledge, has not yet been found effective in enhancing memory in healthy conditions (Stern et al 2014). However, studies in both humans and rodent models reported a rescuing effect of IGF-1, as well as insulin or IGF-2, on cognitive functions in pathological conditions, particularly in cerebrovascular alterations and its role in aging and AD (Liu et al 2001, 2004; Carro et al 2002; Fernandez and Torres-Aleman 2012; Torres-Aleman 2012; Johansson et al 2013; Trueba-Saiz et al 2013), suggesting that IGF-1 and IGF-2 act via distinct mechanisms. Although IGF-1 has been reported to improve memory deficits in aging the data are controversial (for excellent reviews of this subject see Deak and Sonntag 2012 and Sonntag et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies in both humans and rodent models have shown a rescuing effect of IGF1, as well as insulin or IGF2, on cognitive functions in pathological conditions, particularly in mild cognitive impairment or Alzheimer's disease (AD) with insulin (Born et al 2002;Reger et al 2006Reger et al , 2008Sims-Robinson et al 2010), and on cerebrovascular alterations, aging and AD with IGF1 (Liu et al 2001(Liu et al , 2004Carro et al 2002;Craft et al 2012;Fernandez and Torres-Aleman 2012;Torres Aleman 2012;Johansson et al 2013;Trueba-Saiz et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that increasing levels of circulating IGF1 lowers amyloid b (Ab) levels in the brain (Carro et al, 2002). This effect may be the result of the reduced serum-to-cerebrospinal fluid (CSF) traffic of IGF1 reported in both patients with AD (Johansson et al, 2013) and AD mouse models (Trueba-Saiz et al, 2013). However, other authors have demonstrated that reducing IGF1 receptor signalling protects against Ab toxicity in different AD models (Cohen et al, 2009;Freude et al, 2009).…”
Section: Introductionmentioning
confidence: 99%